Global value chains and gender: opportunities and challenges for women workers in developing economies - Barrientos, Stephanie (Papeles de Europa, 2023)
Large retailers and supermarkets operate through global value chains (GVC) in which they directly source goods from suppliers, many in the global south. They coordinate and govern their suppliers via the application of strict commercial requirements and private standards. Gender plays an important role in the commercial dynamics and expansion of retail GVCs. GVCs generate jobs and incomes for hundreds of millions of workers and smallholders in middle and low-income economies, a significant proportion female. Women contribute to enhancing productivity and quality in GVCs, but are unequally recompensed and outcomes for improving their well-being and gender equality are mixed. This paper asks: How are GVCs underpinned by gender relations, and what are the opportunities and challenges for women engaged in African agri-food value chains? It advances a gender perspective on global value chain analysis with a focus on processes of economic and social upgrading and downgrading. It draws on two contrasting case studies involving exports to Europe in which women play critical roles: East African floriculture where wage labour predominates, and West African cocoa sourced mainly from smallholders. It considers the roles of private, social and public governance in promoting more gender equitable economic and social upgrading.